2002
DOI: 10.1007/s00423-002-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral UFT as adjuvant chemotherapy to curative resection of colorectal cancer: multicenter prospective randomized trial

Abstract: It is suggested that the consecutive administration of UFT at 400 mg/day was an effective and highly safe therapeutic method as postoperative adjuvant chemotherapy for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…These results may be attributed to a higher dosage of UFT, rigorous surgical procedures and high quality of the clinical trial. The dosage of UFT per day of 600 mg in this study was greater than the 300-400 mg used in previous UFT studies (Kodaira et al, 1998;Sakamoto et al, 1999;Kato et al, 2002;Meta-Analysis Group, 2004). In this study, TME with lateral pelvic lymphadenectomy was chosen as the control treatment.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…These results may be attributed to a higher dosage of UFT, rigorous surgical procedures and high quality of the clinical trial. The dosage of UFT per day of 600 mg in this study was greater than the 300-400 mg used in previous UFT studies (Kodaira et al, 1998;Sakamoto et al, 1999;Kato et al, 2002;Meta-Analysis Group, 2004). In this study, TME with lateral pelvic lymphadenectomy was chosen as the control treatment.…”
mentioning
confidence: 67%
“…The local recurrence rate in this extended TME was estimated to be lower than simple TME (Akasu and Moriya, 1997;Mori et al, 1998). Although individual RCTs comparing oral fluoropyrimidines with surgery alone showed improvement in both DFS and local recurrence in rectal cancer, but not in OS (Kodaira et al, 1998;Kato et al, 2002), meta-analyses of RCTs related to fluoropyrimidines in the 1980s showed significant benefits in both DFS and OS (Sakamoto et al, 1999;Meta-Analysis Group, 2004). In contrast, there has been no evaluation on DFS and OS in other therapies including 5-FU/leucovorin (LV) and radiation, in Japan.…”
mentioning
confidence: 92%
“…Five relevant trials identified as Japanese Foundation for Multidisciplinary Treatment of Cancer (JFMC) 7-1 (Kodaira et al, 1998), JFMC15-1, JFMC15-2 , Tokai Adjuvant Chemotherapy Study Group for Colorectal Cancer (TAC-CR) (Kato et al, 2002), and National Surgical Adjuvant Study of Colorectal Cancer (NSAS-CC) (Akasu et al, 2006) were included in the metaanalysis involving a total of 2091 patients. In trials JFMC7-1, JFMC15-1, and JFMC 15-2, patients who were randomly assigned to the experimental group received intravenous mitomycin C (6 mg m À2 ) at 1 week and once monthly for 6 months.…”
Section: Selection Of Trialsmentioning
confidence: 99%
“…Patients enrolled in these trials had been followed up for 5 -7 years. Toxicity data were not collected, because detailed analysis of side effects can be found in the published reports of the individual trials (Kodaira et al, 1998;Kato et al, 2002;Watanabe et al, 2004;Akasu et al, 2006). All investigators and the Clinical Trial Committee of all the trials agreed to join in the meta-analysis.…”
Section: Protocol and Data Collection For The Meta-analysismentioning
confidence: 99%
“…Although intravenous administration of anticancer drugs is generally avoided in patients with stage II-Dukes' B colorectal cancer in Japan as in Western countries (Laurie, Moertel, et al, 1989;Moertel, Fleming, et al, 1990), administration of oral Study Group of Japan, 1995;Sakamoto, Hamada, et al, 2001;Muto, Koyama et al, 2002;Kato, Ohashi et al, 2002). Among the various oral fluoropyrimidine preparations, Orzel (UFT+LV Taiho Pharmaceutical Co., Ltd., Tokyo, Japan) has already been approved and is widely marketed in Europe (Mukai, Moriya, et al, 2001;Douillard, Hoff, et al, 2002;Carmichael, Popiela, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%